Effects of nursing support workers participation on negative emotions, quality of life and life satisfaction of patients with cerebral hemorrhage: a quasi-experimental study - Qinglian Luo; Xingzhao Luan; Chengling Xia; Liming Hou; Qisheng Wang; Mingkuan Zhao; Hua Tang; Haowen Zheng; Haiping He; Wei Xiang; Jianmei Wang; Jie Zhou (BMC, 2022)
Abstract Background Due to the high nursing pressure of patients with cerebral hemorrhage and the general shortage of clinical nurses, nursing support workers often participate in clinical nursing work, but the influence of nursing support workers' participation on the negative emotion, quality of life and life satisfaction of patients with intracerebral hemorrhage is unknown. Methods This quasi-experimental study was conducted with a pretest-posttest design. A total of 181 ICH patients admitted to our hospital from January 2022 to April 2022 were enrolled, including 81 patients receiving conventional care (CG control group) and 80 patients receiving nursing support worker participation (RG research group). All patients were recorded with self-perceived Burden Scale (SPBS), Hamilton Depression Scale (HAMD), Quality of Life Scale (SF-36), Somatic Self rating Scale (SSS), Patient self-care ability assessment scale (Barthel) and Satisfaction with life scale (SWLS) scores. Results Patients with high negative emotion were more willing to participate in clinical nursing work (p < 0.05). Nursing support workers involved in cerebral hemorrhage patients can alleviate negative emotions, improve life quality, improve life satisfaction (p < 0.05). Conclusion The participation of nursing support workers can alleviate the negative emotions of ICH patients, enhance their self-management ability, and improve their life quality.